New classification of the facial middle third unilateral outline fractures - Avello, Francisco (2007)
The facial middle third unilateral outline fractures are in general the most frequent fractures of the bony-face bulk, and the superior maxillary and malar having the larger incidence. They occur as a result of severe traumatism. Age, sex and causing agent are the most important factors to determine handling. In some cases they combine with other face fractures. There is more incidence in males, affecting individuals mainly 20 to 40 year-old. Traffic accidents and burglar aggressions are main causes. The facial middle third of the bony-face bulk is conformed by a complex of bones united, mainly the superior maxillary, nasal, malar and temporal bones. We elaborate a classification that includes all mentioned bony structures, comprehensible and for easy application.